A protocol analysis of use of forward and backward reasoning during valuation problem solving. Issue 5 (18th September 2019) - Amidu, Abdul-Rasheed; Boyd, David; Gobet, Fernand
Abstract : Purpose: Behavioural studies of valuers have suggested that valuers rely on a number of cognitive strategies involving reasoning and intuition when undertaking a valuation task. However, there are few studies of the actual reasoning mechanisms in valuation. In other fields, much attention has been paid to forward and backward reasoning, as this shows the choices and decisions that are made in undertaking a complex task. This paper studied this during a valuation task. The purpose of this paper is twofold: first, to develop a methodological approach for empirical research on valuers' reasoning, and, second, to report expert-novice differences on valuers' use of forward and backward reasoning during a valuation problem solving. Design/methodology/approach: The study utilised a verbal protocol analysis (VPA) to elicit think-aloud data from a purposive sample of a group of valuers of different levels of expertise undertaking a commercial-valuation task. Through a content analysis interpretive strategy, the transcripts were analysed into different cognitive segments identifying the forward and backward reasoning strategies. Findings: The findings showed that valuers accomplished the valuation task by dividing the overall problem into sub-problems. These sub-problems are thereafter solved by integrating available data with existing knowledge by relying more on forward reasoning than backward reasoning. However, there were effects associated with the level of expertise in the way the processes of forward and backward reasoning are used, with the expert and intermediate valuers being more thorough and comprehensive in their reasoning process than the novices. Research limitations/implications: This study explores the possibility that forward and backward reasoning play an important role in commercial valuation problem solving using a limited sample of valuers. Given this, data cannot be generalised to all valuation practice settings but may motivate future research that examines the effectiveness of forward and backward reasoning in diverse valuation practice settings and develops a holistic model of valuation reasoning. Practical implications: The findings of this study are applicable to valuation practice. Future training efforts need to evaluate the usefulness of teaching problem solving and explicitly recognise forward and backward reasoning, along with other problem-solving strategies uncovered in this study, as standard training strategies for influencing the quality of valuation decisions. Originality/value: By adopting VPA, this study employs an insightful and rich dataset which allows an interpretation of thoughts of valuers into cognitive reasoning strategies that provide a deeper level of understanding of how valuers solve valuation problem; this has not been possible in previous related valuation studies.